A novel optimal energy management strategy for offshore wind/marine current/battery/ultracapacitor hybrid renewable energy system. (15th May 2020) - Aktaş, Ahmet; Kırçiçek, Yağmur
Abstract: Climate change and high energy demand have significantly increased the need for renewable energy sources (RES). Marine and ocean energy sources draw attention through their high energy potential. Offshore wind and marine current energy is an attractive RES with great potential. The wind and current energy in the marine produces an intermittent and unstable power by nature. Energy storage systems are the most effective solution to minimize power fluctuations in the system and to ensure stable energy demand. This paper presents a novel optimal energy management strategy (NOEMS) for optimal power flow control of the offshore wind/marine current/battery/ultracapacitor hybrid power generation system and for the most efficient harvesting of hybrid renewable energy system (HRES). The proposed NOEMS algorithm calculates as real time the amount of power generated by the HRES and demanded by the load. In this study, nine different dynamic operation modes were considered. Experimental results have shown that the battery and ultracapacitor support to the HRES. In this study, the dynamic behavior of the NOEMS algorithm was investigated by performing a sudden load test from 18 W to 30 W. The NOEMS algorithm shows that the system can minimize power loss, voltage fluctuation, control the charge/discharge status of the battery and ultracapacitor. The proposed algorithm continuously shifts the required power over the hybrid energy storage system to provide the load demand continuously. Graphical abstract: Image 1 Highlights: The hybrid energy storage system is complementary to renewable energy sources. Ultracapacitors prevent the deep discharge of batteries when used with batteries. Optimal energy management algorithm enables more efficient use of source in hybrid renewable energy systems. The unstable power frequency characteristics have been corrected with the hybrid power generation system.